2017
DOI: 10.1086/689871
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mitochondrial Efficiency Explains Mismatched Growth and Metabolic Rate at Supraoptimal Temperatures

Abstract: The relationship between whole-organism growth and metabolism is generally assumed to be positive and causative; higher metabolic rates support higher growth rates. In Manduca sexta, existing data demonstrate a deviation from this simple prediction: at supraoptimal temperatures for larval growth, metabolic rate keeps increasing while growth rate is decreasing. This mismatch presumably reflects the rising "cost of maintenance" with temperature. Precisely what constitutes this cost is not clear, but we suspect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
0
17
1
Order By: Relevance
“…Consequently, some fish on the low ration treatment were actually faster growing than others on the high ration treatment that were consuming three times as much food. While it has previously been shown that increased mitochondrial efficiency promotes fitness-related traits (physical performance [34], growth performance [9,[21][22][23]35], reproductive output [36] and ageing [9,14,36,37]), here we demonstrate that this relationship can even occur when animals are experiencing similar rates of food intake. As well as varying among Table 1.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Consequently, some fish on the low ration treatment were actually faster growing than others on the high ration treatment that were consuming three times as much food. While it has previously been shown that increased mitochondrial efficiency promotes fitness-related traits (physical performance [34], growth performance [9,[21][22][23]35], reproductive output [36] and ageing [9,14,36,37]), here we demonstrate that this relationship can even occur when animals are experiencing similar rates of food intake. As well as varying among Table 1.…”
Section: Discussioncontrasting
confidence: 40%
“…Thus, the higher this ratio, the more efficiently an animal converts its metabolic substrates into ATP, with the ATP then available for energy-demanding cellular processes such as protein synthesis and biomass production [18]. A number of studies have found positive links between mean growth rate and mean mitochondrial efficiency when comparing among treatment groups, populations or selection lines [9,[19][20][21][22][23], but until now there has, to our knowledge, been no assessment of whether mitochondrial efficiency could explain variation in growth rate among individual animals maintained with the same food intake.…”
Section: Introductionmentioning
confidence: 99%
“…Manduca sexta serves as an important model organism for insect physiology and development (e.g. [ 36 , 37 ]) and, in interaction with Cotesia congregata , as a model system for host-parasite interactions and insect immunology (e.g. [ 38 , 39 ]) as well as tritrophic interactions (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, it has also been shown in many studies that for insects, the cost of living is extremely high at stressful high temperatures (>35 • C). For example, the efficiency of the mitrochondria in converting carbohydrate substrates into energy has been shown to drop significantly at stressful high temperatures in Manduca sexta (Martinez et al, 2017). This reduction in mitochondrial capacity is linked with reduction in juvenile stages e.g., larval growth rates, whereby in the case of parasitoids, this may affect their phenology, abundance, and efficacy of host parasitisation.…”
Section: Temperature Effects On Parasitoid Physiology and Implicationmentioning
confidence: 99%
“…Prey (herbivore) diversity is another aspect that has been previously linked with plant nutritional quality (Marzetz et al, 2017). In the study, Martinez et al (2017) postulated three hypothetical scenarios of herbivore response to nutritional quality. First, the growth of the herbivore populations is promoted in diverse communities by co-occurrence of species with complementary nutritional traits.…”
Section: Impact Of Plant Nutritional Quality and Food Web Dynamicsmentioning
confidence: 99%